AWARENESS OF VINCA ALKALOIDS AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2025)
Vincristine along with vinblastine are dual indole-based conjugated Vinca alkaloids formed from foliage of the herb Catharanthusroseus, traditionally known as Vincarosea vincristine , that have been effectively prescribed as single treatment and also in conjunction with other medications in hematological and stable malignancies chemotherapy for tumors. The purpose of this survey was to assess awareness of medical use of vinca alkaloids among dental undergraduate students. A cross-section study was performed with a self-directed survey questionnaire containing 10 queries distributed among 100 dental students. The questionnaire assessed the awareness about vinca alkaloids, their medicinal uses, anticancer activity, mechanism of action and side effects. The responses were recorded and analysed.94% of the respondents were not aware of medical uses of vinca alkaloids.95% were not aware of anticancer activity of vinca alkaloids.97 % were not aware of the mechanisms of action of vinca alkaloids. Again 97% were not aware of side effects of the vinca alkaloids. This study concluded the awareness about the medical use of vinca alkaloids among dental students was poor. Majority of them are not aware of the anticancer activity of vinca alkaloids.